Pedigree comparison highlights genetic similarities and potential industrial values of sugarcane cultivars - Acevedo, Alberto; Tejedor, Matias Tomás; Erazzu, Luis Ernesto; Sopena, Roberto Alfredo; Cabada, Santiago (2017)
Cultivar pedigrees from two sugarcane origins, 9 Argentine (AR) and 7 American (AM) have been reconstructed, and their genetic similarities (based on coefficient of parentage, COP, estimates) show an average of 0.206 ± 0.054. CP clones that enter the pedigrees of AM cultivars are parents or grandparents of AR cultivars, demonstrating that these genotypes have a strong genetic lineage in common. On average, AR pedigrees are smaller and contain less number of founding species than AM pedigrees. However, the lower height of the former is not explained by the different participation of founding species in the pedigrees. The presence of founding species in AR and AM pedigrees increases with the year of cultivar selection, indicating that more founding species entered the pedigree in recently selected cultivars than in older ones. The ancestry of the 16 cultivars trace back to 3 founding species: Saccharum officinarum, S. barberi, and S. spontaneum, with S. officinarum showing the greatest percentage of participation. As S. sinensis participates in 13 pedigrees and S. robustum in 3, the 5 founding species are present in 2 out of 16 pedigrees. Interestingly, the genus Sorghum enters the pedigree of LCP 85-384 pedigree. Industrial parameters assayed indicate that AR and AM cultivars were preferentially selected for their relatively high sucrose content and sugar yield in accordance with two facts: (i) the genetic background and the sucrose genes of sugarcane hybrids provided by the 68% of participation S. officinarum clones, and (ii) no clones of high fiber S. spontaneum have entered the pedigrees in earlier generations.